True Federalism? Illustrations With The Venn Diagram - Kalu, John Otisi (European Scientific Journal, ESJ, 2016)
The growing call for the reinvention of true federalism in many federations reflects the ambiguity inherent in federalism and its practice across countries. This article arises from the controversy it has generated, as to whether there is anything like true federalism or not, where it can be found, and how to determine it. Beyond lending a voice to the debate, this article contributes significantly by simplifying in clear terms, why there exists such calls for true federalism, what depicts it, and what specific factors should be looked out for in order to ascertain the practice of true federalism. By employing the schematics of the Venn diagram, the article creates the templates to visually perceive the interactions between political entities in a federal relation; showing the opposing forces—unification and autonomy— in each entity, which true federalism aims to accommodate, nurture, and safeguard. It concludes that true federalism is the pursuit for unification and maintenance of some levels of independence among different political communities in a given federation, without the attempt by any government to suppress each of these expressions.